Life, Death, and Sanctity of Life according to Islamic Literature and Medical Science: A Comparative Study - Naeem, Aysha; Shah, Prof. Dr. Sultan (Al-Irfan, 2022)
Muslims scrutinize life as a consecration of Allah the Almighty. It is an imperative gift from the Lord for every human being. Islam stresses on asylum and the respect of life of not only Muslims but non-Muslims as well. An Aseptic life is another gift of Allah the Almighty. The last epistle of The Holy Qur’ān, revealed to the Prophet Muhammad (upon whom be peace and greeting) explicits the sanctity of the life of human beings again and again. The recapitulation of verses signifies the prestige of human life. In the contemporary age, research in Medical Science has attained worthwhile importance. The innovations in the field of medical science have made some issues extremely exigent. Such types of mechanical means have been invented which are the substitute for vital functions of life and imitate the functions of some organs of human beings e.g. Respirators, mechanical hearts, and dialysis machines which are capable of continuing a proper functioning life. So it is decisive to present a comparative analysis of life, death, and sanctity of life to prospect their significance according to Islamic literature and medical science to sort out the issues like euthanasia, abortion, infanticide, and removing mechanical support. It also abates the issues for doctors and also makes it effortless for caretakers of the patient.